Pemberdayaan Usaha Mikro Kecil Menengah Bakpia Kirana di Masa Pandemi Covid-19 - Dyah Ariyanti; Nuzul Hikmah; Ahmad Izzuddin; Fitria Esa; Marsetio Wahyu N; Ahmad Fadillah; Rizqy Amalia; Miranti Dian P; Syahrian Barret Y.P (LPPM STIKOM Tunas Bangsa, 2021)
Micro, Small, and Medium Enterprises during the Covid-19 pandemic is due to the reduction of workers in several companies. Micro, Small and Medium Enterprises, also known as MSMEs, are groups that already have small-scale businesses. MSMEs have the potential to grow large so that they are able to absorb labor and reduce unemployment. For this reason, it is necessary to empower this business group to grow well. One of the MSME products in traditional food is Bakpia. The target for this research is Bakpia Kirana MSMEs. This study aims to answer how the process, benefits, and impact of empowering MSME Bakpia Kirana. To identify these problems, the researchers used a qualitative approach, using the method of instrumental observation, in-depth interviews, and documentation. The data analysis used is the data analysis of the Miles and Huberman model which consists of data reduction, data presentation, and drawing conclusions. The results of the study show that Bakpia Kirana managers benefit from empowering MSMEs through capital, infrastructure, marketing support, non-material support, and always reminding them of the main objectives of each activity carried out, and the impact of empowerment has both positive and negative effects. The positive impacts obtained include having income, having more skills, being able to develop a business. The negative impacts include a lot of trade competition among bakpia products which is a benchmark between managers.